FITRAH MANUSIA DAN PEMBELAJARAN MENDALAM: PERSPEKTIF FILSAFAT IBNU SINA - Saeful Ahyar, Ahmad; Nirotul Fikri, A'la; Nisa, Ainun; Fatah, Damanhuri; Mustofa, Ihsan (As-Sulthan Journal of Education, 2026)
Studies on human nature in Islamic education are often understood in a normative-theological manner and have not been fully placed within a systematic philosophical anthropological framework. This article aims to analyze the concept of human nature from the perspective of Ibn Sina's philosophy through a discussion of the structure of the soul, its powers, and the hierarchy of intellect, and to relate it to the deep learning approach in contemporary Islamic education. This research is a literature study with a philosophical approach, using conceptual and interpretive analysis methods on Ibn Sina's major works, particularly Kitāb al-Nafs in al-Shifā' and al-Ishārāt wa al-Tanbīhāt, as well as relevant contemporary academic literature. The results of the analysis show that human nature according to Ibn Sina can be understood as the ontological potential of the soul that develops gradually through the actualization of the powers of the soul and intellect, starting from the potential intellect ('aql hayūlānī) to the acquired intellect ('aql mustafād). This process of intellectual development shows conceptual compatibility with the principles of deep learning, which emphasizes meaningful understanding, reflection, and the development of higher-order thinking skills. This article argues that Ibn Sina's thinking provides a strong philosophical foundation for the application of deep learning in Islamic education, while also enriching the discourse on education in Indonesia, including in the context of the implementation of the Merdeka Curriculum. Thus, the classical concept of human nature is not only theoretically relevant, but also has practical implications for the development of holistic Islamic education.